X-ray generation produced by 500 and 850 MeV electrons in a periodic multicrystal structure created on a GaAs-Plate surface - Zabaev V. N. Viktor Nikolaevich; Kalinin B. N.; Kuznetsov S. I. Sergey Ivanovich; Uglov S. R. Sergey Romanovich (1999, 1999)
В фонде НТБ ТПУ отсутствует